Richard Scarry's Best word book ever. - Scarry, Richard (Racine, Wis. : Golden Books, 1997)
A pictorial vocabulary book with words grouped under common activities such as mealtime and basic concepts such as weather.
"A Golden book, New York.".
1.5
K-3
Keywords: Vocabulary -- Juvenile literature; Vocabulary; Vocabulary